Konsep Cahaya Allah dalam Q.S. An-Nur 24:35 (Analisis Semiotika Roland Barthes) - Muhammad Harfi (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2024)
This paper examines the verse Q.S. An-Nur 24:35 on ‘The Light of Allah’ using Roland Barthes' semiotic theory. The verse compares Allah to a source of light that gives people direction and illuminates the darkness. This study aims to understand the symbolic meaning of the metaphor of light in a spiritual setting and how Muslims understand it in their daily lives using Barthes' ideas of denotation, connotation and myth. The research came to the conclusion that light in the verse is a spiritual symbol that represents God's truth and guidance in addition to being a physical symbol.